Subjective Risk and Participation in Micro Life Insurance in Ghana - Lena Giesbert (German Institute of Global and Area Studies (GIGA), 2012)
This paper analyzes the determinants of households' decisions to purchase micro life insurance, the most common but least investigated type of microinsurance. It uses household survey data collected in southern Ghana in 2009. Insurance participation and extent of coverage are examined against a standard benchmark model, which argues that life insurance uptake increases with risk aversion, the probability of risk, initial wealth, and the intensity for bequests. Many of these predictions indeed hold in the case of micro life insurance. However, the results of probit and tobit models show that nonstandard factors also explain the participation decision. Unlike the case with other available types of insurance, there is a significant negative association between households' subjective idiosyncratic risk perception and the uptake of micro life insurance. Additionally, households' micro life insurance participation is strongly related to their relationships with formal financial services providers and their membership in social networks. These findings suggest that poorer households view microinsurance as a risky option.
Keywords: O16; G21; D12; 330; vulnerability; household behavior; life insurance; Ghana